KINERJA APARATUR SIPIL NEGARA DI KANTOR KECAMATAN DAMPAL SELATAN KABUPATEN TOLI-TOLI - Asrianti; Nuraisyah ambo; Nuraisyah (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Asrianti, Stambuk Number B102 22 075, with the title of research Performance of the State Civil Apparatus at the South Dampal District Office of Toli-toli Regency, was guided by Mrs. Nuraisyah Ambo as the main supervisor and Mrs. Rahmawati Halim as the member supervisor. The purpose of this study was to find out how the performance of the State Civil Apparatus in the South Dampal District Office of Toli-toli Regency. This research was conducted using qualitative research methods with descriptive research type. The informants in this study were determined purposively with the number of informants as many as 10 (ten) people. Data collection techniques through informants accompanied by observation, interviews and documentation. This research uses Suyadi Prawirosentono's theory consisting of 4 aspects to measure the performance of officers which include Effectiveness, Responsibility. Discipline and Initiative. Based on the results of this study, it shows that the performance of the State Civil Apparatus at the South Dampal District Office of Toli-toli Regency, seen from the aspect of Effectiveness, is quite good because it is in accordance with the vision and mission to be achieved, but still needs to be improved again by implementing training on the Apparatus so that the service process runs better and instills a high sense of awareness so that the resulting performance can be maximized in accordance with the predefined goals. In the aspect of Responsibility is quite good, this can be seen from the apparatus that has carried out the duties and functions carried out in the office. Then in the aspect of Initiative, it is good to see that the apparatus has provided suggestions for the progress of the office and the ability of the apparatus to solve problems that occur both in the office environment and in the community. But in the aspect of discipline, the results are still not good and need to be addressed, because judging from some apparatuses who do not obey the rules that should have been understood, such as being late to come to the office, when the break is over, not returning to the office or slowly re-entering and there are also those who leave early. Then in terms of dressing there are some apparatuses that are less uniform.